A tomada de decisão dos sujeitos em projetos organizacionais e em seu cotidiano pessoal: um estudo no contexto de diferentes nacionalidades - Moura, Jose Roberto Carvalho de (2012)
This study aims to investigate the decision-making process of individuals from different nationalities, who work in organizational project management, in their lives out of professional’s context. As the existing methodologies in the area of project management highlight the need of a rational, logical and objective decision-making process, this study will explore if the professionals extrapolate this same linear decision-making process, taken from professional’s sphere, to their daily lives. The academic studies over the years discussed the rational, linear and logical decisionmaking, where they were able to refute this assumption along with new perspectives for the human cognitive’s judgment. Thus, this research will not only present the project management study’s field and its concepts, but also approach the several evolutions of the theory related to decision-making process along the years. Taking into consideration the subjective aspect of the decision theories presented, and cognitive limitation that imposes itself most of the times, this study aims to explore the different heuristics (simplified strategies, mental shortcuts) of judgment and their respective cognitive biases. The three main meta-heuristics, exposed by Tversky e Kahneman in their academic study from 1974 and also focus of this research are, respectively: representativeness, availability and adjustment and anchoring. In this study a quantitative research is performed with organizational individuals who work in project management, or at least had any experience with any projects in the companies they work. It is worth to note this study is not limited to Brazil, as it also extends to other countries containing the same public that are the focus of this research. The results of this research reveal that professionals who work in project management are subject to cognitive biases out of their organizational’s context, considering that Brazilians are less subject to these biases, in comparison to the different nationalities investigated. Also, the research revealed that professional’s experience doesn’t significantly contribute to a rational and logical decision-making in their daily personal lives.